2015
DOI: 10.4049/jimmunol.1500984
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Characterization of the Dysfunctional Immunity and Abnormal Myelopoiesis Induced by Severe Shock and Trauma in the Aged

Abstract: The elderly are particularly susceptible to trauma, and their outcomes are frequently dismal. Such patients often have complicated clinical courses and ultimately die from infection and sepsis. Recent research has revealed that although elderly subjects have increased baseline inflammation as compared to their younger counterparts, the elderly do not respond to severe infection/injury with an exaggerated inflammatory response. Initial retrospective analysis of clinical data from the Glue Grant trauma database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 53 publications
1
57
0
Order By: Relevance
“…Thus, return to homeostasis is a key objective for future immunomodulation therapy of elderly trauma and sepsis patients (33,34,41). However, it is clear that juveniles do not return to baseline genomic expression patterns after severe trauma within 3 days in this study.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Thus, return to homeostasis is a key objective for future immunomodulation therapy of elderly trauma and sepsis patients (33,34,41). However, it is clear that juveniles do not return to baseline genomic expression patterns after severe trauma within 3 days in this study.…”
Section: Discussionmentioning
confidence: 71%
“…We have previously demonstrated that, in response to injury, the elderly do not have an exaggerated inflammatory response nor greater suppression of adaptive immunity genes but, rather, a delayed return to baseline (33,34,41). Thus, return to homeostasis is a key objective for future immunomodulation therapy of elderly trauma and sepsis patients (33,34,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Sperry et al have shown that polymorphism in the IRAK-1 component of the toll-like receptor response is a predictor of organ failure and mortality after severe injury. (25) Therefore, there may be non-hormonal, non-transcriptionally dependent pathways in innate immune signaling that are responsible for differences in the post-injury immune response and subsequent associated organ dysfunction. Given the ontology analysis also identified gene pathways associated with TGF-β response and protein catabolic pathways, it is interesting to hypothesize that changes in these pathways potentially lead to more protein catabolism and lean muscle mass loss and delayed wound healing, which could potentially explain the higher rate of skilled care disposition shown by females in this cohort.…”
Section: Discussionmentioning
confidence: 99%